SERS performance of GaN/Ag substrates fabricated by Ag coating of GaN platforms - Zając, Magdalena A.; Budner, Bogusław; Liszewska, Malwina; Bartosewicz, Bartosz; Gutowski, Łukasz; Weyher, Jan L.; Jankiewicz, Bartłomiej J. (Beilstein Journal of Nanotechnology, 2023)
The results of comparative studies on the fabrication and characterization of GaN/Ag substrates using pulsed laser deposition (PLD) and magnetron sputtering (MS) and their evaluation as potential substrates for surface-enhanced Raman spectroscopy (SERS) are reported. Ag layers of comparable thicknesses were deposited using PLD and MS on nanostructured GaN platforms. All fabricated SERS substrates were examined regarding their optical properties using UV–vis spectroscopy and regarding their morphology using scanning electron microscopy. SERS properties of the fabricated GaN/Ag substrates were evaluated by measuring SERS spectra of 4-mercaptobenzoic acid molecules adsorbed on them. For all PLD-made GaN/Ag substrates, the estimated enhancement factors were higher than for MS-made substrates with a comparable thickness of the Ag layer. In the best case, the PLD-made GaN/Ag substrate exhibited an approximately 4.4 times higher enhancement factor than the best MS-made substrate.
Keywords: GaN/Ag; magnetron sputtering; nanofabrication; pulsed laser deposition; SERS substrates; surface-enhanced Raman spectroscopy (SERS)